Effect of Feeding Artichoke Leaves Meal on Productive and Reproductive Performance of Mandarah Hens - Radwan, Nadia L.; Abdo, Zeinab M.A.; Hassan, R.A. (International Journal of Poultry Science, 2007)
The main target of this study was to evaluate the effect of feeding Artichoke Leaves Meal (ALM) on productive and reproductive performance of Mandarah hens. In this study, a total number of 300 Mandarah hens and 30 Mandarah cocks, 28 weeks of age were randomly distributed into 10 groups and fed on the experimental diets, six levels of ALM (2, 4, 6, 8, 10 and 12% of the diet) in comparison to three tested levels (50, 75 and 100 g/ton diet) of Artichoke Extract (AE), in addition to the basal diet. The results of this study showed that inclusion of Artichoke Leaves Meal (ALM) at 8% of the diet resulted in the highest, values, laying rate, egg mass and best feed conversion than the basal diet (control), while 12% ALM decreased feed intake, significantly as compared with the control and scored the least, numerically, egg mass. The improvements in laying rate, egg mass and feed conversion values, due to 8% ALM, compared to the control were 6.61%, 7.87% and 7.44%, respectively. None of the treatments had adverse effect on the change of body weight of the hen, however artichoke extract levels had no clear effect and may be not enough to cause remarkable effects on productive performance. Shell thickness values (mm) were improved by inclusion of AE or ALM, starting with 75 g/ton AE. There was a gradual, numerically, increase in yolk color score starting with 8% ALM. Artichoke leaves meal at 6,8 and 10% of the diet resulted in the highest fertility and hatchability percentages at the end of the experimental period. It could be concluded that AE at 75 g/ton or more or ALM up to 8% may have beneficial effect on semen quality. Digestibility coefficient of EE was improved by all levels of AE and by ALM up to 10% as compared to the control. Inclusion of Artichoke Leaves Meal (ALM) at 8, 10 and 12% of the diets decreased egg yolk total lipids significantly as compared with the control (232.01-237.94 vs. 264.44 mg/g). Artichoke Leaves Meal (ALM) at 8% decreased yolk total lipids, yolk cholesterol and yolk LDL, in comparison to the control by 10.02, 9.72 and 21.65%, respectively and increased HDL by 14.34%. It decreased serum cholesterol and serum LDL, in comparison to the control by 15.62 and 19.72%, respectively. Best net revenue, economic efficiency and relative economic efficiency values were for 8%, followed by 10% ALM. It is recommended to use 8% artichoke leaves meal to get best economic efficiency, productive, reproductive performance and low cholesterol eggs.